Pesticide Characteristics - Frederick M. Fishel (EDIS)
PI-166, a 3-page illustrated fact sheet by Frederick Fishel, provides a description of the following pesticide characteristics: solubility, adsorption, persistence, and volatility. Includes additional information. Published by the UF Department of Agronomy, July 2008.